Study on green filling mining technology and its application in deep coal mines: A case study in the Xieqiao coal mine - Hou, Junling; Li, Chuiyu; Yuan, Lin; Li, Junbin; Liu, Fei (Frontiers in Earth Science, 2023)
Due to the gradual depletion of shallow mineral resources at present, mines are now gradually entering the deep mining stage. To promote the safe and efficient green mining of deep coal resources and sustainable energy development, and to improve the production efficiency of paste filling mining, the research group has performed this study on the green filling mining technology and application of the working face. Taking working face 1241 (3) of the Xieqiao coal mine as the engineering background, the selection and experiment of filling materials were carried out, and the gangue, fly ash and cement produced by the the Xieqiao coal mine were used as the filling aggregate. Next, the strength changes before and after paste filling was obtained by theoretical calculation. The strength at the early stage of filling was no less than 0.13 MPa, and that at the late stage of filling was no less than 2 MPa. Based on previous experimental research and theoretical calculation, the mixing pumping process of paste material ratio and the gangue crushing process were determined, and the filling pipeline system was designed. Then, based on the traditional coal mining technology, a filling mining technology of working face was designed and optimized. The field application of the research results shows that after the goaf of the working face had been filled, the ground pressure behavior of the coal wall of the working face was significantly weakened, and the stability of the surrounding rock of the working face was effectively controlled. Therefore, the method achieved good results, effectively controlled the stability of surrounding rock in goaf, and provided a theoretical basis and data support for realizing safe, efficient and green mining of deep coal resources. The results of this study bear important significance and application value.